Relationship between Pharmacokinetic Profile and Clinical Efficacy Data of Three Different Forms of Locally Applied Flurbiprofen in the Mouth/Throat - Perlik, Vit; Kulasekaran, Anuradha; Coutinho, Graça; Votava, Martin; Cardot, Jean-Michel (Pharmaceutics, 2023)
This study aimed to link pharmacokinetic (PK) data from different flurbiprofen preparations for the treatment of sore throat with published data to elucidate whether early efficacy is due to the local action of flurbiprofen or a systemic effect after absorption of the swallowed drug. Three comparative bioavailability studies conducted in healthy subjects provided data from flurbiprofen 8.75 mg formulations, including spray solution, spray gel, lozenges, and granules. A parallel interstudy comparison was made of PK parameters, including partial AUCs (pAUCs), using an ANOVA model with the calculation of 90% confidence intervals (CI) for the differences between least squares (LS) means for each of the test groups versus the respective reference groups. All three studies showed bioequivalence for the respective product comparisons. The interstudy comparison showed a slower rate of absorption for granules compared to spray solution (reference) based on Tmax, Cmax, and pAUCs for 1 h and 2 h. When AUC0.25h and AUC0.5h were considered, slower rates of absorption were also seen for lozenges and spray gel. The differences correlated with the reported time of onset of action, which is faster for the spray solution (20 min) compared to lozenges (26 min) and granules (30 min). These pAUCs provide useful data that allow for the discrimination between formulations. Moreover, the pAUC values represent <5% of the total AUC, suggesting that the early onset of pain relief is a response to immediate local absorption at the site of action rather than a systemic effect.
Keywords: pharmacodynamic; locally applied locally acting; throat; LALA; lozenge; pharmacokinetics; flurbiprofen; GIT